Pengaruh Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi (Studi Pada Perusahaan Manufaktur Industri Barang Konsumsi) - Embun Suryani; I Nyoman Nugraha Ardana P; Qurrota A’yuni (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
The purpose of this study was to examine the effect of profitability and liquidity on firm value with dividend policy as a moderating variable, because several previous studies showed different results. In this study, the population is manufacturing companies listed on the Indonesia Stock Exchange, totaling 51 companies. Sampling was carried out using the purposive sampling method, so that 24 samples were obtained for 3 years of observation (2017-2019). The research data was obtained from the Indonesia Stock Exchange website. Data analysis was performed using multiple linear regression analysis. The results of this study indicate that profitability and liquidity have a significant effect on firm value. Furthermore, dividend policy strengthens the relationship between profitability and liquidity to firm value.